Attitudes and behaviours on digital health technologies: evidence from the Opinion Study in Portugal - Bobrowicz-Campos, E.; Lima, M. L.; Camilo, C.; Rodrigues, R. B.; Espanha, R.; Martins, H. (The 5th International European Social Survey (ESS) Conference, 2024)
Objective: In this communication we present findings from the Opinion Study in Portugal, carried out in the context of the 10th round of the European Social Survey, which offers the first comprehensive view on attitudes and behaviours of Portuguese towards digital health technologies (DHT) and its key determinants. Methods: The study sample consisted of 403 individuals (58% Female, 42% Male) with 18 years old or above and with Internet access. Data was collected through online interviews carried between September and October 2022. Attitudes of interest included: ease of DHT use, importance attributed to DHT, distrust towards DHT, concerns about the quality of care, and preference for face-to-face or digital care. Behaviours of interest included: use of DHT in specific services in the last three months and adherence to health apps. To learn about the prevalence of attitudes and behaviours in the study sample, descriptive analyses were conducted. The relationship between attitudes and behaviours and sociodemographic variables was examined by means of multiple regression analyses. Results: Attitudes towards DHT showed to be quite positive, although not in relation to all aspects considered. Namely, most respondents evaluated DHT as easy to use, important, and trustworthy (68%, 58% and 54%, respectively). There was also greater preference for digital care (45%) as compared to face-to-face care (23%). However, regarding the quality of care, more than half of the sample (57%) expressed concerns about the possibility of its reduction resulting from the DHT use. In relation to behaviours towards DHT, their prevalence was quite variable, being more expressive for the use of services included in the regular functioning of the health system, and less expressive for the use of apps on one’s own initiative. Namely, most respondents reported that, in the last three months, at least once, they had received an electronic prescription, visited the website of General Directorate of Health and/or made an appointment with a health professional via computer or mobile phone (79%, 66% and 51%, respectively). However, the participation in a consultation with a health professional using a digital device was mentioned by only 21% of respondents. Comparatively, the adherence to health apps was around 40% for managing medical prescriptions and scheduling and reminding health appointments, not exceeding 14% for checking and managing clinical symptoms or promoting health and well-being. Negative attitudes and less frequent behaviours were consistently associated with older age, lower level of education, lower level of health literacy, and lower income. Discussion: This is the first study in Portugal that aims to understand the attitudes and behaviours of Portuguese towards DHT. The findings point to an overall favourable orientation towards DHT. They also show that the use of DHT in specific services and specific health apps are not yet very prevalent. However, these findings must be regarded with caution, as the study was conducted among Portuguese who have access to the Internet, possibly underestimating the perspectives of those for whom this access is limited. Further studies should address this gap. The present study also identifies important signs of social inequality in digital health. Based on these findings, we recommend elaborating measures to mitigate the identified inequalities, so that the digital transformation in healthcare leaves no one behind.